Praktik Jual Beli Sperma Sapi ( Studi Kasus Di Desa Bukit Cermin Hilir Kecamatan Dolok Masihul Kabupaten Serdang Bedagai) - Tri Hidayatullah (Bahasa Indonesia, 2026)
This study aims to analyze the practice of buying and selling cow sperm among livestock farmers in Bukit Cermin Hilir Village and to examine the validity of this practice from an Islamic legal perspective, particularly within the context of contemporary Islamic jurisprudence (fiqh muamalah). The study employed field research with a descriptive qualitative approach to obtain a comprehensive overview of the transaction mechanisms taking place in the field. Data collection was conducted through direct observation of artificial insemination activities, in-depth interviews with livestock farmers, artificial insemination officers, and related parties, as well as a documentary study of relevant regulations and literature. The results indicate that the practice of buying and selling cow sperm is carried out as part of the application of artificial insemination technology aimed at improving the genetic quality, productivity, and economic value of livestock. Transactions are conducted with frozen semen that has been processed, packaged, and has a clear size and quality so that it can be optimally utilized by livestock farmers. From an Islamic legal perspective, this practice remains a matter of debate among Islamic scholars. Some scholars argue that buying and selling sperm is impermissible because it is considered to contain elements of gharar (unlawful) and the object is not originally suitable for sale. However, other opinions permit such transactions on the grounds that the sperm has been separated from the animal's body, has a tangible benefit, its quality and quantity can be identified, and it meets the principle of benefit. Based on the research findings, the practice of buying and selling cow sperm can be considered valid under Islamic law as long as it meets the pillars and requirements of the contract, is conducted transparently, does not contain elements of fraud, and provides benefits to all parties. This research is expected to contribute to the development of contemporary Islamic jurisprudence (fiqh) studies and serve as a reference for livestock breeders, artificial insemination practitioners, and policymakers